Addressing persistent racial discrimination in personnel selection: strategies to foster inclusion in the workplace - Rodriguez-Acosta, Fabio J. M. (2024)
According to INEI's National Household Survey 2021 (ENAHO), 73% of Peruvians have suffered discrimination in the workplace. What is even more alarming is that 56% of these reported cases are directly attributed to the person's physical appearance. In that sense, the objective of this study is to highlight the current challenges in eradicating racial discrimination. The study employed a comprehensive methodology that included conducting an extensive literature review on discrimination in the workplace. The findings identified highlight disparities in employment opportunities based on race and ethnicity, as well as in the workplace. It is concluded that racial discrimination is a persistent problem in hiring practices and the workplace, which has a negative impact on equality and diversity.